A randomised assessment of the pharmacokinetic, pharmacodynamic and safety interaction between apixaban and enoxaparin in healthy subjects - Barrett, Yu Chen; Wang, Jessie; Song, Yan; Pursley, Janice; Wastall, Philip; Wright, Robert; LaCreta, Frank; Frost, Charles (Thrombosis and Haemostasis, 2012)
Following major orthopaedic surgery, guidelines usually recommend continued thromboprophylaxis after hospitalisation. The availability of an effective oral anticoagulant with an acceptable safety profile that does not require routine clinical monitoring may lead clinicians to switch patients from subcutaneous to an oral therapy either during hospitalisation or at discharge. The purpose of this study was to assess the effect of enoxaparin on the pharmacokinetics, pharmacodynamics and safety of apixaban, an oral, direct inhibitor of coagulation factor Xa. In this four-period, crossover study, 20 healthy subjects were randomised to receive single doses of apixaban 5 mg orally; enoxaparin 40 mg subcutaneously; apixaban 5 mg and enoxaparin 40 mg concomitantly; and apixaban 5 mg followed 6 hours (h) after by enoxaparin 40 mg. Pharmacokinetics of apixaban were not affected by enoxaparin. Average peak pharmacodynamic effect, measured by anti-Xa activity, was 1.36 U/ml after administration of apixaban and was 0.42 U/ml after enoxaparin. Following co-administration of apixaban and enoxaparin, peak anti-Xa activity was 42% higher than for apixaban alone. Following administration of enoxaparin 6 h after apixaban, peak anti-Xa activity was 15% higher than for apixaban alone. In conclusion, enoxaparin had no effect on the pharmacokinetics of apixaban. The increase in anti-Xa activity after co-administration was modest and appeared to be additive. Peak anti-Xa activity increases are mitigated by separating administration of subcutaneous anticoagulation and apixaban when switching between therapies; the potential for pharmacodynamic interaction may be further mitigated by transitioning at the next scheduled dose (12 h).
Keywords: Apixaban; factor Xa inhibitor; drug switching; pharmacokinetics/pharmacodynamics; thromboprophylaxis